Philip Roth, Novels 2001-2007 – The Dying Animal, The Plot Against America, Exit Ghost (ENTHYMEMA, 2013)
Review of Roth, Philip. Novels 2001-2007 – The Dying Animal, The Plot Against America, Exit Ghost. Ed. Ross Miller. New York: The Library of America, 2013. Print.